Measuring the Cultural Difference in Individual Attitude Towards Risk - Tetenova, Evgeniia; Špecián, Petr; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
Weber, Blais and Bets (2002) found that difference in risk attitudes and behaviour can depend on the context: individuals can change risk attitude across different domains. Among these domains are financial, which consists of investment and gambling, social, recreational, health/safety and ethical. The aim of this thesis is to investigate the differences in risk attitudes between the Czech Republic and Russia. For this purpose data for the empirical analysis was gathered using a questionnaire based on Domain-Specific Risk-Taking (DOSPERT) Scale proposed by Weber, Blais and Betz (2002). The collected data were analyzed using linear regression, following Weber, Blais and Betz (2002) and Breuer et al. (2013). The main findings revealed that there is a difference in risk attitude: the participants from Russian sample tend to be more risk-seeking in financial domain, especially in gambling, than the respondents from Czech sample. Also interesting finding is that Russians are more interested in getting profit or any other kind of benefits from the participation in risky activities, while Czechs decide to engage in risky activities by first taking into account their individual perception how risky these activities could be.
Vedoucí práce: Petr Špecián
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses